Antara Partisipasi dan Mobilisasi: Perempuan dalam Kancah Politik Praktis di Kabupaten Jembrana, Bali - I Nyoman Sukiada (Universitas Udayana, 2018)
Representation of women in Jembrana Regency Legislative Institution in 2009 election reached 20%. Although it has not reached 30% in accordance with the mandate of Law No. 10 of 2008, the representation of women in the Legislative Institution of Jembrana Regency is the highest among the regencies/cities in Bali. When closely examined, the participation of women in the political sphere has deconstructed itself due to a struggle of power and mobilization. Automatically the law that sets the quota of women’s involvement in practical politics is 30%, especially those si ing in the legislative institution can signal a practice of mobilization. Within certain limits, the process of mobilization appears in the election of women legislators, because women are not really interested in practical politics, but are mobilized by the state, political parties and by the closest people such as husbands. The paper aims to explain the election of female legislators in Jembrana Regency Legislative Institution which indicates that there has been a struggle of power between participation and mobilization.